BUDAYA LITERASI DAN PEMANFAATAN SOSIAL MEDIA PADA MASYARAKAT AKADEMIK - Muhamad Tisna Nugraha (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2017)
Incresingly and rapidly technology progress encouraging on more improving user amount of internet base services. Various features on internet base services creating people start to change from conventional media forms books, megazines and newspapers into online base media. Not only as consumer, some becomes part of spreading information especially in social network. Then,from this services people can share thoughts, opinions, knowledges, ideas or communications sharing only without knowing time and place. Although on the other side social media existence not always have positive impact, some part of it individually or group using this services as way to do various criminal acts, other has pragmatic characters and apathetic with social media as long as not bothering personal interests. Based on this,the writing will peeling more about how utilization social media on community especially on academician community aspects. Key words: literation, social media and academician community.